Pengembangan Produk Pariwisata Dalam Mewujudkan Branding Pariwisata Kabupaten Samosir - Mohamad Ridwan (LOSARI Jurnal Arsitektur, Kota dan Permukiman, 2021)
This study aims to analyze and development of existing tourism products in Samosir regency in realizing the branding of tourism Samosir regency. The research method used in this research is qualitative method with descriptive analysis technique. Research findings: (1). Culture is the main attraction in Samosir regency. (2). The existing tourist facilities in Samosir district is adequate and meet from the needs and desires of tourists. (3). Accessibility in Samosir Regency still does not meet from the aspect of quality, so it needs improvement or better development again.